2017
DOI: 10.1186/s12886-017-0627-8
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic retinoblastoma of the parotid and submandibular glands: a rare case report

Abstract: BackgroundRetinoblastoma is the most common intraocular malignancy occurring in children. It can metastasize to the regional lymph nodes, central nervous system and distant organs usually the bones and bone marrow and very rarely to the soft tissue. Here, we report a case of unilateral retinoblastoma in a 4-year-old girl accompanied by a large metastasis of the parotid and submandibular glands that developed about 6 months previously and gradually increased in size 5 months after enucleation of the left eye.Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…[1] They form 5% of the primary skeletal tumors. [2] Metastasis though uncommon is usually seen with recurrences. Curettage with intralesional adjuvant therapy with polymethylmethacrylate, liquid nitrogen, and bone graft has been successfully used to reduce recurrences while preserving function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] They form 5% of the primary skeletal tumors. [2] Metastasis though uncommon is usually seen with recurrences. Curettage with intralesional adjuvant therapy with polymethylmethacrylate, liquid nitrogen, and bone graft has been successfully used to reduce recurrences while preserving function.…”
Section: Resultsmentioning
confidence: 99%
“…According to various studies, RB could metastasize within 6 months of onset of symptoms, if left untreated. [2] Therefore, delay in diagnosis may result in poorer outcome. We have analyzed the clinicopathological profile of children diagnosed with RB in our institute, primarily to understand the epidemiology and also to study the relationship between advanced disease and delayed presentation.…”
Section: Introductionmentioning
confidence: 99%
“…With these treatments, the 5-year survival rate of RB patients has greatly improved. However, the mortality of RB is still as high as 70% in developing countries because of the occurrence of advanced and metastatic tumors, accounting for approximately 9-11% (Balmer et al, 2006;Dimaras et al, 2015;Wang et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have confirmed that RB metastasizes to the parotid glands and submandibular lymph nodes through lymphatic vessels, but there are few previous case reports. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Previously, there have been some reports of successful RB treatment in the metastatic stage. Wang et al, 9 Purkayastha et al 10 have reported the successful treatment of RB patients with parotid gland and soft tissue metastasis by systemic IVC combined with local radiotherapy. Wang et al, 11 Vempuluru et al, 12 and others reported the use of systemic IVC combined with external radiotherapy for the treatment of RB patients with bone metastasis and CNS metastasis.…”
Section: Discussionmentioning
confidence: 99%